DETECCIÓN DE POBLACIONES DE RHAGOLETIS POMONELLA (DIPTERA: TEPHRITIDAE) DURANTE LA FRUCTIFICACIÓN DE CRATAEGUS MEXICANA (ROSACEAE) EN PUEBLA, MÉXICO - Hernández-Ortiz, Vicente; Morales, Irma; Vergara, Carlos (Instituto de Ecología, A.C., 2004)
An assessment of the Rhagoletis pomonella populations was made to detect the critical period of infestation of the "tejocote" (Crataegus mexicana) during its fruiting and maturation. The study was conducted in four localities in Huejotzingo Municipality, Puebla. Adult populations were monitored by use of 64 McPhail traps distributed among the four localities during 15 weeks (from September to December 1997), while estimation of infestation levels in fruits were estimated by sampling 1,680 mature fruits throughout the study. Results showed that most captures of adults were from the early part of September to the beginning of October (during the first five weeks of the study), when most fruits had attained their full development and ripeness was initiated. Statistical results showed no significant differences of captures among sampled sites (F(2,42)= 1.58, P= 0.21), unless respect to temporal distribution (weeks), difference of significance was observed (F(14,42)= 5.53, P< 0.001). The total of captures among traps showed that adult populations had an aggregate distribution, because only some traps at each locality accounted for most of the captures. On the basis of our results, we discuss the time periods of higher susceptibility of the tejocote to infestation by R. pomonella in this region.